PERLUASAN SRATEGI PEMASARAN BAGI PRODUK HOME INDUSTRI MELALUI PENGUATAN DAYA SAING DI DESA KUBAH SENTANG KECAMATAN PANTAI LABU - Julienda Br Harahap; Tika Indria; Shofwan Andri; Lusi Elviani; Farida Khairani Lubis (Jurnal Pengabdian Mitra Masyarakat, 2023)
Economic growth can be achieved according to the target if a planned and structured business is carried out. One way is to encourage the creation of more entrepreneurs. Entrepreneurship is considered as the answer to overcome economic problems, especially to encourage economic growth and technological development. Apart from having an impact on increasing economic growth, entrepreneurial activity is also related to creating jobs. Another effort to strengthen the economy of the Indonesian people is through collaboration between universities and the business world, in this case focusing on MSME actors. Universities must be able to take a role in efforts to increase the potential of MSME actors through the results of research and studies conducted. The results of this research and study are expected to be able to bring about a change in the form of new creativity and innovation in the business world so as to provide benefits for MSME actors and the community. Apart from innovation and creativity, MSME actors also need to be given an understanding of product marketing in order to strengthen the competitiveness of selling community products as an effort to achieve economic independence. Therefore, the FEB UISU Entrepreneurship and Accounting study program conducted Community Service activities in Kubah Sentang Village, Pantai Labu District, Deli Serdang Regency. The method of implementing this training and mentoring mainly uses the method of action research activities. The implementing team carried out the activity of providing material while carrying out an analysis to solve the problems encountered. The material giving method is carried out by lectures, interactive question and answer, demonstrations and solving cases.